Model to enhance knowledge sharing process in academia during COVID-19 - Zainab Amin Alsulami; Hayder Salah hashim; Zaid Ameen Abduljabbar (Bulletin of Electrical Engineering and Informatics, 2022)
Knowledge sharing (KS) is considered one of the essential processes of knowledge management (KM). Recently, the emerging Web 2.0 technologies were used by academicians and students for KS during the COVID-19 pandemic. The purpose of this study is to identify the factors that affect the knowledge-sharing process through Web 2.0 (KSWT 2.0) technologies and their impact on academic performance within higher educational institutions (HEIs) in Iraq. The technology-organization-environment (TOE) theory was used in this study to develop the conceptual framework. The population includes students and academicians at Basrah University in Iraq. Using stratified random sampling, a total of 415 academicians and students participated in this study. The results revealed that the most significant factors that positively affect KSWT 2.0 technologies were the technological factor such as relative advantage, compatibility. From the organisational factor academicians’ skills and knowledge, and from environmental factor, the peer pressure. In addition, the results proved that the KSWT 2.0 technologies positively maximised academic performance. The results presented in this study are valuable for Iraqi universities that implement or aim to use Web 2.0 technologies in the knowledge-sharing process.